“I would have said ‘bad news’ but now I say ‘different news”: Mixed methods evaluation of a communication skills training for healthcare professionals in the first 1000 days of life - Esther Mugweni; Tamsyn Eida; Tracy Pellat-Higgins; Sabrena Jaswal; Melita Madden; Angela Emrys-Jones; Sally Kendall (PLoS ONE, 2025)
Background Receiving a diagnosis of congenital anomalies in the first 1000 days of life can have significant implications for a family’s emotional and mental wellbeing. We refer to this as different news. We evaluated a communications skills training to improve how healthcare professionals deliver different news using a train-the-trainer (Champions) model. Methods We recruited 22 healthcare professionals from 6 NHS trusts in England and trained them as Champions. They delivered 17 training sessions to healthcare professional colleagues. Data were collected on knowledge, skills and attitudes to different news communication using a bespoke questionnaire and the Self-Efficacy Scale (SE-12) at pre-training, straight after training and four weeks post-training. We conducted 19 interviews with healthcare professionals, four managers and eight parents. Data were analysed using Framework analysis guided by the Theoretical Domains Framework. Results A total of 204 healthcare professionals completed pre-training questionnaires, 187 completed post-training questionnaires immediately after training, and 109 completed the questionnaires four weeks post-training. A total of 179 healthcare professionals completed the SE-12 scale immediately after training and 102 completed it at four weeks follow-up. The training improved healthcare professionals’ confidence and skills to deliver different news. There were statistically significant differences in confidence levels between pre-/post-training SE-12 scores in delivering different news. Scores were significantly higher post-training. The estimated difference in mean scores post-training was 18.3 (95% confidence interval 15.7–20.9 p < 0.001), and one-month post-training 16.9 (95% confidence interval 13.7–20.2; p < 0.001) more than three times larger than the difference in SE-12 in the validation sample. There was a statistically significant difference between SE-12 scores for the Champions and the healthcare professionals they trained. SE-12 scores were higher for Champions and their improvement from pre-training was greater. Overall, participants reported that the training provided the skills to structure different news conversations, use the right language and pace the provision of information and support. Conclusions The results suggest that the training equips healthcare professionals to deliver different news to families sensitively and compassionately which can potentially prevent mental ill-health across the life course.